Simulation in Nursing Education: A Narrative Review of Strategies, Outcomes, and Challenges - Agustini, Ni Luh Putu Inca Buntari; Suyasa, I Gede Putu Darma; Israfil, Israfil; Indrayani, Ni Luh Dwi; Artsanthia, Jintana (STIKES Adi Husada, 2025)
Simulation-based education is a vital component of modern nursing education, providing a safe, controlled environment for students to develop clinical competencies. It bridges the gap between theory and practice by fostering experiential learning, critical thinking, and decision-making. This narrative review explores simulation strategies in nursing education, assesses educational outcomes, and identifies implementation challenges. A literature search was conducted in PubMed, Scopus, CINAHL, and ScienceDirect for articles published between 2020 and 2025. Studies discussing simulation strategies, outcomes, and barriers in undergraduate nursing education were included. Common simulation methods include high-fidelity manikins, standardized patients, virtual simulations, and hybrid models. These approaches enhance clinical skills, communication, teamwork, confidence, and knowledge retention. Simulation also supports reflective practice and safe error correction. However, barriers such as high costs, limited faculty expertise, time constraints, and inconsistent evaluation methods persist. Simulation enhances learning outcomes in nursing education but requires strategic integration, adequate resources, and faculty training. Addressing these challenges can maximize its impact and better prepare students for clinical practice. The outcome of this review highlights that well-implemented simulation strategies significantly improve nursing students’ clinical competence, critical thinking, and readiness for real-world healthcare environments, ultimately contributing to safer and higher-quality patient care.